Crime victims’ rights commissioners: public interest entities in a regulatory regime - Kirchengast, Tyrone (International journal of comparative and applied criminal justice, 2021)
The legal force of crime victims’ rights is ambiguous: are they service standards or legal rights? This question has created confusion about the nature of compliance and bifurcates the enforcement mechanism as administrative or legal. Regulatory analysis creates a wider lens to this debate. In this article, we conceive victims’ rights charters as part of a regulatory regime designed to influence the conduct of state agencies in discharging their functions. Rights compliance and enforcement as a regulatory challenge provides a framework for systematic analysis of regulatory instruments, tools and strategies chosen by key actors. We use a case study of statutory crime victims' rights commissioners in Australia to illustrate the implications of these choices. We suggest that clearer articulation of the techniques of compliance show the coexistence of administrative and legal sanctioning. Our argument turns attention to the duties imposed on public institutions of criminal justice and their accountability.